The Impact of Early Marriage in the Fulfilment of Women Rights - Pratiwi, M Riska Anandya Putri (The Indonesian Journal of International Clinical Legal Education, 2020)
Early marriage still occurs in some areas. In Kedungrejo Village, Gabus Sub-district, Grobogan District, there are still many young men or women who are married in their young age. Of course, there are marriage factors that influence and cause some impact on the personal community. Problems in this research is apasaja factors that can encourage early marriage and how the impact of early marriage to condition of society around in Kedungrejo Village, Grobogan District Purwodadi Regency. The purpose of this research is to describe factors driving the marriage dinidan to know the impact of early marriage. The method used in this research is qualitative research method with case study approach and data source come from early marriage and parents of perpetrators. Methods of data collection is done by observation as well as interviews with sources related to the case. Results from research on marriage case dinidi Karangrejo Village District Gabus Grobogan District that the majority of them still do early marriage. This is due to several driving factors that cause the occurrence of early marriage one of the factors of parents as well as educational factors. So from these driving factors cause some positive impact and negative impact of Early Marriage.